Evaluation of Si/BC3 nanotube complex as anode materials for Li-ion battery - a DFT-D study - Kwan, Wai Yee. (2010)
The possibility of Si/BC3 nanotube complex as potential anode materials for Li-ion battery was evaluated by first principles calculation based on density functional theory with dispersion correction (DFT-D). Li atom can adhere well on the inner and outer surfaces of BC3 nanotubes and the most stable adsorption site is hollow site of either C6 or B2C4 rings. This agrees well with the previous literature reports. Both single Si atom and Si dimer adhere much stronger on the inner and outer surface of BC3 nanotubes than Li does, indicating that the formation of Si/BC3 nanotube complex is feasible. The most stable absorption sites are hollow site of B2C4 ring for single Si atom and hollow – hollow, between hollow and top – between hollow and top of B2C4 ring or bridge – bridge in C6 ring for Si dimer. The presence of Si on the BC3 nanotube does not reduce the Li diffusion barrier indicating that steric effects (the size of the rings in sidewall) play a critical role. This factor may hinder the application of Si/BC3 nanotubes as potential anode materials for Li-ion battery.